TYPE 2 DIABETES MELLITUS, ANEMIA, AND HYPERTENSION AS THE RISK FACTORS THAT AFFECT THE INCIDENCE OF METASTATIC BREAST CANCER - Elma Elmika; Selamat Budijitno; Ari Suwondo (Universitas Airlangga, 2022)
Background: Breast cancer is one of the most common gynecologic malignancies in women and the main cause of death in 25% of all cases. The main cause of death from breast cancer is metastases, it is estimated that 5-10% of breast cancers have metastasized at the time of early diagnosis with an advanced stage. Purpose: To analyze the risk factors that influence the incidence of metastases in patients with advanced breast cancer. Methods: This study is an analytic observational study with a cross-sectional design, the number of samples in the study was 120 patients. The inclusion criteria of the study sample were breast cancer patients with advanced stages III and IV in the last five years. Exclusion criteria were incomplete patient medical records. The sampling technique in this study was consecutive sampling. This research was conducted at Ibnu Sina Hospital, Makassar City. The variables analyzed in this study were type 2 diabetes mellitus, anemia, and hypertension which were tested with the chi-square test. Results: The results of this study showed that diabetes mellitus type 2 (p=0.00; Prevalence Rate [PR]=1.79; 95% CI=1.32-2.42) and anemia (p=0.03; Prevalence Rate [PR] = 1.82; 95% CI = 1.61-2.86) is a risk factor that affects the incidence of metastases in patients with advanced breast cancer. While the risk factor that has no effect is hypertension. Conclusion: Type 2 diabetes mellitus and anemia are risk factors that influence the incidence of metastases in breast cancer patients.